Community empowerment through the processing of crispy catfish in Padukuhan XII Sidorejo, Bantul - Amrih, Dewi; Sutakwa, Adi; Syarifah, Atika Nur; Nadia, Lana Santika (Community Empowerment, 2021)
Padukuhan XII Sidorejo, located in Kasihan District, Bantul Regency, was one of the areas that was cultivating a lot of fish and vegetables in buckets or budikdamber during the Covid-19 pandemic. One of the vegetables cultivated is kale and can meet daily household needs. While the type of fish that is widely cultivated with budikdamber is catfish. Cultivation of catfish and vegetables is expected to meet household needs, but consumption of catfish from this cultivation is less than optimal due to low knowledge about diversification of processed catfish. These potentials and problems in the community were further explored by the UPY Agricultural Product Technology Bachelor Program lecturer team through community service programs to provide basic knowledge about processed catfish production. This crispy catfish can be a variation of the daily food menu and/or creative business ideas in the food sector for the residents of Pedukuhan XII Sidorejo, Bantul.